A diffusion tensor magnetic resonance imaging study of brain tissue from patients with migraine. Issue 4 (1st April 2003) - Rocca, M A; Colombo, B; Inglese, M; Codella, M; Comi, G; Filippi, M
Abstract : Objective: To measure in vivo, using diffusion tensor magnetic resonance imaging (DT-MRI) the extent of pathological damage of normal appearing brain tissue (NABT) from patients with migraine. Methods: Dual echo and DT-MRI scans of the brain were acquired from 34 patients with migraine and 17 sex and age matched healthy volunteers. Mean diffusivity (MD) and fractional anisotropy (FA) histograms of the NABT were obtained from all subjects and the histograms' peak heights and average NABT MD and FA measured. When present, average MD and FA values of T2 visible lesions were also measured. Results: In comparison with healthy volunteers, patients with migraine had lower MD histogram peak height (p=0.02) of the NABT. No differences were found in FA histogram derived metrics between migraine patients and healthy subjects. No difference was found for any MD and FA histogram derived metrics between migraine patients with and without brain MRI lesions, and between patients with and without aura. Conclusions: This study shows that, although brain damage may extend beyond T2 weighted abnormalities in patients with migraine, the severity of these "occult" changes is mild compared with that found in other diseases associated with white matter abnormality.